Motivation for Early Cervical Cancer Detection in Fertile Women - Ismarwati, Ismarwati; Wahyuntari, Evi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Background: Cervical cancer is the second most common cancer in Indonesia, after breast cancer. The aim of this study was to look into the motivation for early cervical cancer detection in women of childbearing age. Methods: Asequential explanatory design was used in this mixed method study. Aquasi-experimental non-equivalent control group design was used in the quantitative study. Working area in 4  Community Health Center,  total sample of 40 for each group who were given vidio in the treatment group and given booklets to the control group. Qualitative research is determined by purposive sampling. There were 29 informants consisting of 15 informants in the treatment group and 14 informants in the control group. Results: 30% of respondents were ready to conduct checks prior to treatment, compared to 17.5 % in the control group. There was an increase of 87.5 % after the treatment, compared to 20.0 % in the control group.. Conclusion: Internal motivation to implement early detection of cervical cancer feels risk, wants to know personal health and maintains personal health against cervical cancer and there is a change in the value of willingness before and after intervention using WhatsApp